Análise da política de remuneração na atividade leiteira : estudo de caso em uma pequena propriedade rural no município de Serafina Corrêa/RS - Maestri, Rafael (2022)
The management of rural properties has presented several challenges in the face of new economic and production scenarios. Dairy activity is one of the main forms of production in family farming and is constantly developing. The present study aimed to evaluate the remuneration policy of the dairy activity of a property in the interior of Serafina Côrrea - RS. The property has as activities the cultivation of corn, wheat and sorgo, totally linked to dairy cattle, with Dutch cattle. For its elaboration, a quantitative research was used, classified as descriptive, with primary characteristics allowing data collection and documentary. Through this case study, a survey of revenues and expenses was made in the period from the 2nd half of 2018 to the first half of 2022. After analyzing the remuneration received in the dairy activity, it started from a loss of -R$10,751.16 in 2018 to a profit of R$97,418.73 in 2022, and a net margin of -2.64% in 2018 to 15.63% in 2022. When the amount paid for the liter of milk in the same period was evaluated, it increased by 51.92%. Milk is a very volatile product, both a month can give profit and can give damage, so it is necessary for the manager to know its production costs very well, besides being aware of every change that occurs, always seek the best pricing and aim to reduce its costs. Therefore, it was suggested that the owner continue with the dairy activity, using accounting as a control tool, thus finding ways to reduce production costs, and causing it to increase its profit more and more. These suggestions aimed to contribute to the search of owners for better results.